ANALISIS POSITIONING RUMAH MAKAN KHAS BANJAR BERDASARKAN PERSEPSI KONSUMEN (Studi Pada Warung Makan Fauzan, Warung Makan Mona dan Warung Makan Idah Jaya di Banjarmasin) - Prihatini Ade Mayvita; Rizka Zulfikar (Jurnal Ekonomi dan Manajemen, 2018)
This study aim is to get an overview of the competitive landscape, consumer perception andperceptual gap between consumer perception of product and attributes that offered by Banjarethnic restaurant in Banjarmasin. This research object are Warung Makan (WM.) H. Fauzan,WM. Mona and WM. Idah Jaya. The population is Banjarmasin community with a sample sizeof 50 was determined by purposive sampling technique. Data analysis using quantitativedescriptive method and analysis of MDS (Multi-dimentionalScaling) with the help of IBM SPSSsoftware Ver. 23. The results showed that (1) WM. H. Fauzan has the position above thanWM. Mona and WM. Idah Jaya in consumer perceptions attributes such as physical condition,service, support and distribution facility locations. Additionally WM. H. Fauzan also has theadvantage that the typical grilled fish sold using a sauce or condiment (original) and has thehighest branch between the typical food stall Banjar other dishes, (2) WM. Mona hasadvantages in service, product, and pesonaltraits. (3) WM. Idah Jaya only has advantages inpromotional attributes, price and location.